A machine learning analysis of psychopathological features of Eating Disorders: a retrospective study - Graziella Orru; Mario Miniati; Ciro Conversano; Rebecca Ciacchini; Laura Palagini; Mauro Mauri; Angelo Gemignani (Mediterranean Journal of Clinical Psychology, 2021)
Background: The clinical presentation of Eating Disorders (EDs) is often characterized by a great phenotypic variability and by a substantial instability over time of diagnostic categories. For these reasons, it has been proposed a different approach to EDs, encompassing both their dimensional and categorical descriptions, in a lifetime perspective, namely the ‘Anorexic-Bulimic Spectrum’ (ABS). Here we report a retrospective study with the interview built and validated for the assessment of ABS signs and symptoms, the ‘Structured Clinical Interview for Anorexic-Bulimic Spectrum’ (SCI-ABS), administered together with the ‘Mood Spectrum Self Report’ (MOODS-SR), a questionnaire able to assess sub-threshold mood spectrum dysregulations often comorbid with EDs signs and symptoms.